Mites of the family Phytoseiidae Berlese from Kenya (Acari: Mesostigmata) - El-Banhawy, E. M.; Knapp, M. (Zootaxa, 2011)
We surveyed the phytoseiid mites in four different geographical zones of Kenya: Zone I, upper highland and tropical alpine (2400–4400m); Zone II, lower highland (1800–2400 m); Zone III, midland (800–1800 m); Zone IV, tropical, hot and humid (0–800 m). A total of 107 species was found. In the subfamily Amblyseiinae there were 14 species in the genus Neoseiulus Hughes, one in Asperoseius Chant, one in Paraphytoseius Swirski & Schechter, five in Typhlodromips De Leon, five in Transeius Chant & McMurtry, one in Graminaseius Chant & McMurtry, 11 in Amblyseius Berlese, one in Arrenoseius Wainstein, two in Typhlodromalus Muma, seven in Ueckermannseius Chant & McMurtry, one in Amblydromalus Chant & McMurtry, 20 in Euseius Wainstein, one in Iphiseius Berlese, one in Phytoseiulus Evans and one in Gynaeseius Ehara & Imano. In the subfamily Phytoseiinae Berlese, there were four species in the genus Phytoseius Ribaga. In the subfamily Typhlodrominae Wainstein, there were four species in the genus Kuzinellus Wainstein, and 27 in Typhlodromus Scheuten.